Environmental life cycle assessment as a tool for process optimisation in the utility sector - Corvalán, Sergio M. (2005)
A methodology is presented to calculate the optimum operating conditions of a petrochemical plant utility sector, to minimize the overall Life Cycle Environmental Impact. The battery limits of the system studied are extended to include the relevant environmental impacts corresponding to the electricity imported generated in thermoelectric, hydroelectric and nuclear plants. The Overall Environmental Impact is calculated as a weighted sum of the following Potential Environmental Impact categories: Global Warming, Acidification, Eutrophication, Photochemical Oxidation, Ozone Depletion, Human Toxicity and Ecotoxicity. The contribution of each component emission to these environmental categories is evaluated multiplying its flow rate by the corresponding Heijungs factor. A Mixed Integer Non Linear Programming problem is formulated and solved in GAMS. Global Warming is the most relevant contribution. Significant reductions in the Overall Environmental Impact and particularly in Global Warming are achieved selecting the pressure and temperature of high, medium and low pressure headers and the optional drivers that can be electrical motors or steam turbines. Improvements are also reported in the operating cost, natural gas, water and electricity consumption.